Rapid determination of branched chain amino acids in human blood plasma by pressure-assisted capillary electrophoresis with contactless conductivity detection - Tůma, Petr; Gojda, Jan (Electrophoresis, 2015)
A CE method with contactless conductivity detection has been developed for the clinical determination of the branched chain amino acids (BCAAs) valine, isoleucine and leucine in human blood plasma. The CE separation was performed in an optimised BGE with composition of 3.2 M acetic acid in 20% v/v methanol, pH 2.0. The achieved separation time was 125 s when using a capillary with an effective length of 14.7 cm, electric field intensity of 0.96 kV/cm and simultaneous application of a hydrodynamic pressure of 50 mbar. The separation efficiency in blood plasma equalled 461 000 theoretical plates/m for valine and isoleucine, and 455 000 theoretical plates/m for leucine; the detection limits are equal to 0.4 μM for all three amino acids. The RSD values for repeatability of the migration time equalled 0.1% for measurements during a single day and 0.3% for measurements on different days; the RSD values for repeatability of the peak areas equalled 2.3-2.6% for measurements during a single day and 2.7-4.6% for measurements on different days. It followed from the performed tests that the plasmatic levels of BCAAs attain a maximum 60 min after intravenous application of an infusion of BCAAs.
Keywords: lineární modely; Limit of Detection; Amino Acids, Branched-Chain; Clinical analysis; limita detekce; Humans; elektrická vodivost; Electrophoresis, Capillary; klinická studie jako téma; Clinical Studies as Topic; Female; dospělí; lidé; elektroforéza kapilární; reprodukovatelnost výsledků; Diabetes Mellitus; Adult; ženské pohlaví; Reproducibility of Results; Insulin; Electric Conductivity; Linear Models; Contactless conductivity detection; větvené aminokyseliny; diabetes mellitus; Diabetes mellitus; CE; Amino acids; inzulin